(untitled) (Research, Society and Development, 2025)
Introduction: This study presents an important reflection on the psychological impacts of the postpartum period, from a psychoanalytic perspective. Motherhood represents a profound phase of transformation in a woman’s life, involving not only physical changes but also emotional and identity-related ones. Objective(s): The aim of this study is to investigate the psychological impacts of the postpartum period, focusing on emotional challenges, the mother-baby bond, the marital relationship, and the importance of psychological support. Method: This is a qualitative literature review, based on the psychoanalysis of Winnicott and Melanie Klein, which analyzes the postpartum period through the axes of postpartum depression, support network, maternal bonding, and marital relationships. Articles from 2015 to 2025 were selected from the Scielo, Pepsic, and Google Scholar databases. Inclusion criteria: empirical studies and reviews published in scientific journals. Methodological quality was assessed using the JBI tool. Result: 24 studies were included in the analysis. The findings highlight the processes experienced during motherhood, both in psychological and physical dimensions, emphasizing factors such as postpartum depression and the quality of the marital relationship. The presence of a support network proved to be a relevant element in the maternal experience. Predominantly, the studies pointed to the impacts and experiences of the postpartum period in multiple areas of a woman’s life. Conclusion: Becoming a mother in the postpartum period is a profound process of transformation, in which a woman needs to rebuild her identity in the face of new challenges and responsibilities. This transition is neither linear nor free of difficulties; it involves dealing with intense emotions, insecurities, and the need for physical and emotional adaptation.